Konstruksi Pencitraan Cagub Ridwan Kamil Dan Partai Nasdem Melalui Iklan Politik - Herry Setianto Wahyono; Taufiq Furqon Nurhakim (Program Studi Hubungan Masyarakat Politeknik LP3I, 2023)
This research wants to see about Cagub Ridwan Kamil and Nasdem imaging that is done through advertisements on television. This research analyzes the new Indonesian version of political advertising text and the legal version by using Teun van Dijk's discourse analysis, which includes analysis in terms of text (Visual and Audio-Visual). The results of this study reveal that Cagub invites the public to join together in making changes in law enforcement that is fair and civilized. In order to carry out the process of imaging party politics, audiences also read the image of their party differently based on their subjectivity, either based on the experiences and associations they bring, or because of the influence of the setting in which the image appears. This, in assessing the political image of each candidate for governor, some are positive and some are negative and some are even neutral, depending on their respective subjectivity